Image Edge Detection Using FPGA (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Medical imaging often involves the injection of contrast agents and subsequent analysis of tissue enhancement patterns. X-ray angiograms are projections of 3D reality into 2D representations, there is a fair amount of self occlusion among the vessels, hence one cannot extract the vessels directly using the image intensities or gradients (edge) alone. Vessels extraction from angiogram images is useful for blood vessels measurement and computer visualizations of the coronary artery. This project describes the algorithm for automatic segmentation of coronary arteries in digital X-ray projections here an improved k-means algorithm is proposed. The performance of the proposed algorithm is compared with other techniques. Â A methodology for implementing real-time DSP applications on a field programmable gate arrays (FPGA) using Xilinx System Generator (XSG) for Mat lab is presented in this paper. It presents the architecture for Edge Detection using Sobel Filter for image processing using Xilinx System Generator. The design was implemented targeting a Spartan3 a DSP 3400 device (XC3SD3400A-4FGG676C) then a vertex 5 (xc5vlx50-1ff676) .the edge detection methods has been verified successfully with no visually perceptual errors in the resulted images.